Fetal membrane architecture, aging and inflammation in pregnancy and parturition. (April 2019) - Menon, Ramkumar; Richardson, Lauren S.; Lappas, Martha
Abstract: Preterm birth is the single major cause of infant mortality. Short and long term outcomes for infants are often worse in cases of preterm premature rupture of the fetal membranes (pPROM). Thus, increased knowledge of the structure characteristics of fetal membranes as well as the mechanisms of membrane rupture are essential if we are to develop effective treatment strategies to prevent pPROM. In this review, we focus on the role of inflammation and senescence in fetal membrane biology. Highlights: Fetal membranes provide structural support for the growing fetus. Senescence and inflammation can weaken the fetal membranes. Targeting inflammation may prevent rupture of the membranes.